Retrospective Study on School Children with Deleterious Oral Habits - M, APARNA.; RAMAKRISHNAN, MAHESH; V, RAKSHAGAN (The journal of contemporary issues in business and government, 2021)
Oral habits are repetitive behaviour in the oral cavity that results in malalignment of the dentofacial structure and they include digit sucking ,lip sucking, lip biting, nail-biting, bruxism, self- injurious habits, mouth breathing and tongue thrusting. This study was taken to assess the prevalence of deleterious oral habits among school children.A Sample size of 6200 patients under 3 to 15 years of age were taken into study. Their case records were reviewed and retrieved from patients reported to a private Dental Hospital, India. Details regarding their demographic information and presence or absence of oral habits were collected. Statistical analysis was done using SPSS ( version 26.0) .Prevalence rate among school children with deleterious oral habits was evaluated. Overall 27 % of the school going children had deleterious oral habits.Nail biting (28.52 %) habit was most commonly seen followed by thumb sucking habit ( 19.39 %) , Mouth breathing habit (19.01 %), Tongue Thrusting habit (17.87 %) and Lip biting habit (15.21 %).Higher prevalence of these oral habits among children were seen in this study population.This highlighted the need for preventive orthodontic treatment at an early age of life, so that future occurrence of malocclusion can be avoided.